Metode Social Story pada Pembelajaran PAI untuk Meningkatkan Perilaku Positif Siswa Autis di Homeschooling Cordova - Umama; Aries Musnandar (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The Islamic religious education was important things for all the students especially for elementary level. It’s be expected from the Islamic science and knowledge to guidance in the next life. Even more to the students with autism syndrome, it will be more important for them. They have many difficullities in their communications, social interactions dan behaviours, so make the problem in accepting the kwonledge. Bassed on researches dan technologies, many kind of intervention will be solution for this problem. And social story is one of the various solution in it. This study has purpose to describe the planning, implementation and evaluation of Islamic religious education learning with the social story method to increase the positive behavior of autistic students. at Cordova Homeschooling, and to determine the positive behavior of autistic students that could be improved. It’s used descriptive qualitative method with a case study approach. The techniques for collecting data is interview, observation, and documentation, that analyzed by condensing, displaying, and drawing conclusions, and checked by triangulation for validity. The result for this study is that planning of this method is includes purposes, materials, strategies, and learning media. The implementation is uses the social story method with image media and supported by verbal explanations, repetition, prompting, reinforcement, and tests. The evaluation is uses learning program evaluation routinely. The positive behaviors can be improved in cognitive aspect and practice one.